Isozyme patterns and protein profiles in neuromuscular disorders. Issue 3 (June 1982) - Edwards, Y H; Tipler, T D; Morgan-Hughes, J A; Neerunjun, J S; Hopkinson, D A
Abstract : The isozyme patterns of six different enzymes and the polypeptide profiles of soluble proteins have been examined in muscle biopsy specimens from 74 patients with a wide variety of neuromuscular disorders. About half of the samples showed unusual features in at least one, and often several, of the enzymes and proteins tested. The extent of the biochemical abnormalities was roughly proportional to the severity of the disorders. In all cases the unusual isozymes and polypeptide profiles seemed to reflect a reversion to the fetal pattern of gene expression. However, this change appeared to occur in extant muscle and was not dependent on the appearance of new muscle fibres. Among the enzymes, phosphoglycerate mutase followed by creatine kinase appeared to be the most sensitive index of muscle disorder. The extent of the change in the muscle creatine kinase isozyme pattern was not correlated with the levels of serum creatine kinase activity.